2022
DOI: 10.1021/acs.jafc.2c06931
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Induces Intestinal Barrier Dysfunction by Regulating the FXR-Mediated MLCK Signaling Pathway in Mice and in IPEC-J2 Cells

Abstract: Aflatoxin B1 (AFB1) is a widespread mycotoxin in food and feed. Although the liver is the main target organ of AFB1, the intestine is the first exposure organ to AFB1. However, the mechanism by which AFB1 induced intestinal barrier dysfunction via regulating the farnesoid X receptor (FXR)-mediated myosin light chain kinase (MLCK) signaling pathway has rarely been studied. In vivo, AFB1 exposure significantly decreased the small intestine length and increased the intestinal permeability. Meanwhile, AFB1 exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The first organ to be exposed to AFB1 is the intestine, which weakens the intestinal cell viability and disorders the expression of tight junction proteins, weakening the intestinal barrier [ 23 ]. In this study, we obtained the same results.…”
Section: Discussionmentioning
confidence: 99%
“…The first organ to be exposed to AFB1 is the intestine, which weakens the intestinal cell viability and disorders the expression of tight junction proteins, weakening the intestinal barrier [ 23 ]. In this study, we obtained the same results.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, OTA treatment decreased FXR mRNA and protein expressions in kidney and HK-2 cells, consistent with the recently published paper that AFB1 suppressed FXR protein expressions in the liver of mice and IPEC-J2 cells. 39,40 Besides, this work used the FXR activator GW4064 to boost FXR expression. GW4064 reversed the increase in BUN, CRE, and UA levels, Ntn-1, Kim-1, TNF-α, IL-1β, and IL-6 mRNA levels, decrease in IL-10 mRNA level, and lessened pathological injury of the kidney induced by OTA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Mycotoxins cause a major health hazard to both animals and humans, and a recent increase in the male reproductive disorder has been related to the increased occurrence of mycotoxins in food and the environment . AFB 1 is a mycotoxin that can contaminate agricultural products and accumulate in livestock and poultry through the enrichment in the food chain, causing serious food safety problems . Our previous study found that AFB 1 decreased testis coefficients, and damaged testicular morphology of mice. , One of the main functions of the testis is to synthesize T. Reduced T biosynthesis caused by AFB 1 is the main factor that induces reproductive dysfunction and male infertility; , however, the precise mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%